The influence of parent–child attachment on school adjustment among the left-behind children of overseas Chinese: The chain mediating role of peer relationships and hometown identity - Zhang, Huilan; Li, Zihan; Yan, Xiaoqiu; Deng, Chunkao (Frontiers in Psychology, 2022)
Background:Transnational parenting of left-behind children are a kind of vulnerable children in the eastern coastal areas of China. Previous studies have shown that there are problems in their school adjustment. This study explored the relationship between parent-child attachment and school adaptation among the left-behind children of overseas Chinese parents, as well as the chain mediating role of peer relationships and hometown identity. Methods: A total of 1,047 students in grades 3-8 from 5 schools in Zhejiang Province were selected by cluster sampling. The surveys were compiled from the Inventory of Parent and Peer Attachment, the Adaptation subscale of the Adolescent Mental Health Quality Questionnaire–Chinese Version, the Hometown Identity Scale, and the Student Peer Relationship Scale. Results: The results showed that there was a significant positive relationship between parent-child attachment and school adjustment of overseas left-behind children.More importantly, this linkage was chain-mediated by peer relationships and hometown identity. Conclusion: This study revealed the mediating mechanisms of peer relationships and hometown identity in the parent-child attachment and school adjustment of left-behind children and provides empirical support for future interventions.